FROM THE HISTORY OF AGRARIAN REFORMS OF THE KOKAND KHANS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
This article analyzes some aspects of the construction of water facilities in the Kokand Khanate, water facilities built in the territory of the Khanate in the 18th and 19th centuries, their use, farming culture, water distribution and management rights. The measures of Erdonabi , Norbotabi , Olimkhan , Umarkhan , Muhammad Alikhan's regarding agricultural issues are discussed .